The influence of the Prescription Act, 68 of 1969 on selected aspects of the notice in terms of Section 129(1)(a) of the National Credit Act, 34 of 2005 - Van Heerden, C.M. (Corlia) (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.